The Marketization of Childhood: A Critical Examination of Sharenting in the Digital Age - Beata GOTWALD; Bogdan GREGOR; Marlena KOWALCZYK (Communications of International Proceedings, 2024)
This paper critically examines the phenomenon of sharenting – the practice of parents sharing children’s personal information and images on social media – and its implications within the digital age. The purpose of this article is to critically examine the phenomenon of sharenting, exploring its implications within the digital age, including the commodification of childhood, ethical dilemmas, and its role in the marketing ecosystem, while highlighting the need for greater awareness and regulation to protect children’s rights and autonomy. Sharenting has gained significant traction due to advancements in technology, evolving perceptions of parenting roles, and the normalization of sharing private moments online. Drawing on a multidisciplinary review and qualitative interviews with micro-influencers, the study highlights the duality of sharenting as both a tool for personal expression and a marketing strategy. It explores the commodification of childhood through sharenting and the ethical dilemmas it poses, including privacy violations, digital footprint permanence, and parental control over children’s identities. The findings reveal that sharenting is deeply embedded in the marketing ecosystem, influencing consumer behavior and creating new opportunities for brand visibility. However, parents' motivations often blur the lines between self-expression and commercial exploitation, raising questions about consent, ethical boundaries, and the long-term psychological impact on children. Additionally, the study identifies emerging trends in the digital construction of childhood, where social media reinforces idealized representations of family life and perpetuates consumerist ideals. The paper concludes by calling for greater awareness and regulation to balance the benefits of digital connectivity with the need to protect children’s rights and autonomy. Future research should focus on the financial dynamics of sharenting, the evolving role of children as content creators, and the broader societal implications of this practice in the digital economy.
Keywords: Sharenting; Digital Childhood; Digital Footprint; Marketing Ecosystem